A Transferrin Triggered Pathway for Highly Targeted Delivery of Graphene‐Based Nanodrugs to Treat Choroidal Melanoma. Issue 16 (29th June 2018) - Zhao, Bingxin; Dong, Kalun; Lin, Mimi; Dong, Gongxian; Shan, Suyan; Lawson, Tom; Yan, Lu; Zhang, Wenjing; Shi, Bingyang; Chou, Shulei; Baker, Mark S.; Liu, Yong
Abstract: The synthesis of transferrin (Tf)‐modified pegylated graphene (PG) and its application as a highly efficient drug delivery carrier for therapy of Ocular Choroidal Melanoma‐1 (OCM‐1) cells is presented. For the first reported time, nanoscaled PG is prepared using an environmentally friendly ball‐milling technique. The unique 2D nanostructure obtained using this PG synthesis approach offers considerable advantages in terms of drug loading and delivery, as well as the conjugation of Tf to PG providing a more targeted delivery vehicle. A highly efficient targeted pathway toward OCM‐1 cells triggered by an affinity between Tf and Tf receptors expressed on the surface of OCM‐1 cells is reported first here. PG‐Tf is observed to easily anchor anticancer drugs such as doxorubicin via π–π stacking. This work performs a Transwell two cells coculture experiment, a 3D in vitro tumor model, and an in vivo mouse model with OCM‐1 tumors to demonstrate the composite's therapeutic superiority over conventional systems for the targeted delivery and controlled release of antitumor drugs. Abstract : A highly efficient targeted delivery pathway into tumor cells based on the endocytosis transmembrane movement is mediated by transferrin and transferrin receptors. Pegylated graphene prepared by an edge‐functionalized ball milling method is used to provide an efficient nanovehicle for the delivery of transferrin and antitumor drugs. More than 80% tumor cell inhibition and efficient pH‐dependent drug release is realized.